(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
It highlights the importance of research through its focus on the assessment of tax for settling accounts Mmakhr medicines and annual statement controls and its role in determining the taxable income of the real tax Mmakhr drugs and achieve tax equity through tax settling accounts. The tax authority relies annual controls laid down by the tax settling accounts for Mmakhr medicines despite their inclusion bookkeeping business No. 2 system for the year 1985 average .ually this basis formulated hypothesis (that the adoption of the tax authority on annual controls in the tax settling accounts for Mmakhr medicine does not contribute in determining income taxable real tax for this Almmakr). the resulting search for a number of conclusions and recommendations, and the most important conclusions is that the annual special controls Bmmakhr medications do not achieve justice for both sides, financial power and Mmakhr medications because of their reliance on the assumption and guesswork. As recommendations, it is the most important of the tax authority must adopt the books business tax in settling accounts for Mmakhr medicines because they are covered by commercial bookkeeping system No. 2 for the year 1985 and work on the audit and ensure the integrity of their data and the extent of compliance with real profits.